Lid wiper epitheliopathy: The influence of multiple lid eversions and exposure time. Issue 3 (June 2019) - Shaw, Alyra; Collins, Michael; Huang, Justine; Nguyen, Huu My Phuong; Kim, Zion; Lee, Grace; Johnstone, Joshua; Casey, Ashleigh
Abstract: Purpose: To investigate the effect of multiple lid eversions on lid wiper epitheliopathy (LWE), along with the effect of cumulative lid exposure time and the patterns of associated staining. Methods: The increase in area of lid wiper staining with lissamine green was compared by everting both the upper eyelids of each subject (i.e. contralateral design), with one eye being everted once for 45 s and the fellow eyelid everted three times, each time for 15 s. This pattern of contralateral eversion was repeated with a total of three eversions in one eye and nine eversions in the fellow eye, with each eye totalling 135 s cumulative exposure to eversion over about 9 min. The LWE area of staining was objectively quantified from slit lamp photography images captured at every lid eversion by 2 masked observers. Two-way repeated measures ANOVAs were used to determine the effect of number of lid eversions and cumulative exposure time on the amount of staining caused. Each image was also categorized into its primary LWE staining pattern, by a masked observer. Results: The multiple eversions condition caused significantly greater LWE than the single eversion condition (p < 0.001), while cumulative exposure time did not have a significant effect on LWE (p = 0.137). Classification of the primary staining patterns revealed that with more eyelid eversions there was a shift from mostly 'no staining' to minor patterns ('short horizontal bands' and 'vertical streaks') and then to more extensive patterns ('broad horizontal bands' and 'comb-shaped'). Conclusions: The number of eyelid eversions is a confounding factor that should be controlled when investigating LWE, in particular when considering the link with dry eye or contact lens discomfort. However the cumulative exposure time did not appear to influence the LWE magnitude.